2016
DOI: 10.1186/s41155-016-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Projective aspects on cognitive performance: distortions in emotional perception correlate with personality

Abstract: Several approaches in psychology converge with the concept that individual characteristics may interfere with the perception and interpretation of the world. We hypothesized that such phenomenon could be identified in instruments that were not only projective techniques. The research's goal was to study perceptive distortions in a cognitive test and their relations with personality instruments. Responses from 222 participants in the Computerized Test of Primary Emotions Perception (PEP) were rated in distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
6
Order By: Relevance
“…Besides, there was a correlation between more hours playing and lower attribution of joy to emotional expressions, which may be related to less interest in contact with others, according to other studies with emotional perception (Miguel & Pessotto, 2016). This result indicates a propensity for social isolation and the little experience of joy given a large number of hours in-game activity.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Besides, there was a correlation between more hours playing and lower attribution of joy to emotional expressions, which may be related to less interest in contact with others, according to other studies with emotional perception (Miguel & Pessotto, 2016). This result indicates a propensity for social isolation and the little experience of joy given a large number of hours in-game activity.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies (Miguel & Pessotto, 2016) have shown that there is an association between these distortions and personality traits rather than cognitive aspects. Also, there is an association between the general distortion in the test and being less able to correctly perceive reality.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Em uma pesquisa feita com não surdos em aplicação individual (Miguel & Pessotto, 2016), os resultados sugeriram que perceber mais alegria estaria relacionado a maior interesse no contato social, mais medo estaria relacionado à necessidade de autonomia, mais tristeza estaria relacionado a menos problemas de autoestima, e mais raiva estaria relacionado à desconfiança, sentimentos de solidão e pensamentos agressivos. Surpresa e curiosidade não foram investigados naquela pesquisa, e os surdos da presente pesquisa não perceberam amor e nojo em níveis significativamente distintos.…”
Section: Discussionunclassified
“…Além disso, deve assinalar se a emoção expressa é autêntica ou falseada. Pesquisas anteriores foram desenvolvidas com o PEP, que mostraram adequadas características psicométricas e validade com construtos relacionados e divergentes (Miguel, Finoto, & Miras, 2013;Miguel, Ogaki, Inaba, & Ribeiro, 2013;Miguel & Pessotto, 2016;Miguel & Primi, 2014).…”
Section: Instrumentosunclassified